Effect of hydrothermal aging on color stability and translucency of two zirconia generations compared to lithium disilicate ceramics - Atef Ahmed Elzoughary; Tamer Abel Rahim Hamza; Mohamed Fawzy Metwally (Journal of Dental Research, Dental Clinics, Dental Prospects)
Background. An esthetically acceptable ceramic restoration should have optical properties like the teeth and reflect, transmit, and absorb light. The present investigation compared how hydrothermal aging affected the properties of two types of zirconia and lithium disilicate. Methods. Thirty rectangular samples (12×14×1 mm) were prepared and sectioned from three different ceramic blocks/blanks (n=10), then assigned into three groups according to the ceramic type: group Z: IPS e.max ZirCAD prime, gradient zirconia (3Y/5Y-TZP); group K: Katana UTML (5Y-TZP); and group E: IPS e.max CAD (lithium disilicate). Color analysis of samples was performed before and after hydrothermal aging (1, 3, and 5 hours) using a spectrophotometer. Color difference (∆E00), translucency parameter (TP00), and contrast ratio (CR) were evaluated. The microstructural analysis was performed using x-ray diffraction (XRD). Data were statistically analyzed at a significance level of P<0.05. Results. A statistically significant variation was observed across means of ∆E00, TP00, and CR at different times. Group Z displayed the highest statistically significant mean ∆E00. Group E demonstrated the greatest statistically significant mean TP00. Group K exhibited the most statistically significant mean CR. Conclusion. Hydrothermal aging significantly affected the optical characteristics of lithium disilicate and zirconia ceramics. The translucency of samples increased with aging.